Interactions and management for the future of marine aquaculture and capture fisheries. Issue 2 (6th February 2019) - Clavelle, Tyler; Lester, Sarah E.; Gentry, Rebecca; Froehlich, Halley E.
Abstract: Aquaculture surpassed wild fisheries as the largest supplier of fish for human consumption in 2014 and is expected to supply the majority of seafood for future increases in demand. Marine and coastal aquaculture, collectively referred to as mariculture, currently represents just 36% of aquaculture production but is poised to expand in the decades ahead. One of the most commonly cited concerns regarding this likely expansion is ecological and socioeconomic interactions with wild‐capture fisheries. While attention has largely been drawn to high‐profile negative externalities from fed finfish and crustacean mariculture, not all marine‐based practices are equivalent. Empirical evidence for the different interactions between mariculture and wild fisheries is often sparse. While negative consequences can arise, positive synergies can also occur. By considering mariculture development in the context of fisheries interactions, we suggest that it is possible to minimize conflicts and maximize positive connections between the two sectors. We provide the first comprehensive synthesis of the interactions between mariculture and wild fisheries, characterizing the types of interactions, evaluating available empirical evidence and identifying where management (sector‐specific and cooperative) can play an important role. We highlight potential effects of mariculture on the efficiency, sustainability, and equity of seafood production and identify remaining knowledge gaps.